Lycium Barbarum Polysaccharide Attenuates Acute Toxicity Caused by Titanium Dioxide Nanoparticles in Splenic and Pulmonary Tissues - Amal Sewelam; Soad L. Kabil; Bashir M. Jarrar; Mohamed Sabry; Manal Morsy (Tabriz University of Medical Sciences, 2024)
Background: Titanium dioxide nanoparticles (TiO2NPs) are widely used in various commercial and industrial applications, posing potential risks to human body. Lycium barbarum polysaccharide (LBP) is renowned for its antioxidant and anti-inflammatory properties. This study aims to investigate the protective potential of LBP against TiO2 NPs-induced acute toxicity in splenic and pulmonary tissues. Methods: Forty rats were grouped as follows: Group I, the normal control, received daily 0.1% DMSO intraperitoneally (ip) and 0.5 mL PBS orally. Group II received LBP (100 mg/kg/day) by gavage for 14 days. Group III received a single ip injection of TiO2 NPs (972 mg/kg) on the 8th day. Group IV obtained both LBP and TiO2 NPs. Group V was treated with LBP, TiO2 NPs and Zinc protoporphyrin IX (ZnPPIX), the later was injected ip in a dose of 10 mg/kg/day one hour before LBP. Biochemical, histopathological, and immunohistochemical analysis were conducted on splenic and pulmonary tissues of all rats. Results: TiO2 NPs induced congestion, inflammation, macrophage proliferation, pyknosis and significantly increased caspase-3, CD68, NF-κB, TLR4 immunoexpression with upregulation of markers of oxidative stress, inflammation, apoptosis and fibrosis. Pretreatment with LBP mitigated TiO2 NPs-induced tissue damage but enhanced heme oxygenase-1 (HO-1) mRNA expression. Co-administration of ZnPPIX reversed LBP protective impact. Conclusion: LBP demonstrated the ability to alleviate splenic and pulmonary injuries caused by the acute TiO2 NPs toxicity. LBP prevents TLR4/NF-κB mediated injury triggered by TiO2 NPs through HO-1 upregulation. Further research is required to explore the preventative role of LBP against both acute and chronic toxicity brought by nanomaterials in general and TiO2 NPs in particular.